A randomized comparative study of artemisinine (qinghaosu) suppositories and oral quinine in acute falciparum malaria. - Arnold, K; Tran, T; Nguyen, T; Nguyen, H; Pham, P (1990)
In adult patients with acute falciparum malaria in Ho Chi Minh City, Vietnam, a more rapid reduction in parasite count (50% clearance in 11.3 h) and complete clearance (41.8 h) was obtained in 32 adult patients randomly assigned to received artemisinine suppositories than was obtained with 30 patients receiving oral quinine (20.8 h and 68.1 h). There were higher degrees of resistance (RII, 3 cases; RI early, 1 case) with quinine than with artemisinine but in a subgroup of patients quinine reduced parasitaemia as rapidly as artemisinine (50% clearance 13.6 h and 10.1 h respectively). Recrudescence (RI, delayed), occurred in 16 patients receiving artemisinine compared with 6 receiving quinine. Artemisinine suppositories, because of ease of administration, efficacy, and lack of side effects or risk of overdose, have advantages for the early treatment of falciparum malaria by possibly reducing the morbidity and mortality associated with a high or sustained parasitaemia.